Some problems in response of the criminal law to environmental crimes - Samardžić Stefan (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
It is more than three decades since the Serbian criminal law provides direct protection to the environment. On the other hand, it seems that environment today is most the contaminated ever. From the two previous premises we could expect a large number of the environmental criminal cases, but the pre-researches to this paper lead us to the different conclusion. Could we rely on the criminal law and to which extent in the protection of the environment?.